The keybox: Shape-frame fitting during tool use in Goffin’s cockatoos (Cacatua goffiniana) - Habl, Cornelia (PLoS One, 2017)
The ability to move an object in alignment to a surface develops early in human ontogeny. However, aligning not just your own body but also the object itself in relation to a surface with a specific shape requires using landmarks rather than the own body as a frame of reference for orientation. The ability to do so is considered important in the development of tool use behaviour in human and non-human animals. Aside from humans, with the exception of a single study on habitually tool using primates, shape-frame matching abilities remain largely unstudied. The Goffin's cockatoo is a generalist parrot, and not a specialised tool user but has shown the capacity to innovate and use different types of tools under controlled settings. We tested these parrots in a tool selection and tool use task featuring objects and their corresponding substrate grooves in a number of shapes with different levels of symmetry. Subjects had to choose the correct ‘key‘ to insert into a box, and align its shape to fit into the corresponding ‘keyhole’ in the box. The parrots were able to select the correct key above chance level from early on in the experiment. Despite their lack of hands, they required fewer placement attempts than primates to insert simple object shapes into corresponding grooves. For complex shapes, they reduced their insertion effort by rotating shapes in their beak while avoiding as many protrusions as possible. Unrewarded play experience with similar object shapes was provided to some of the subjects previously to testing, but did not seem to have an effect on the number of correct choices or on insertion effort.